P-selectin antibody treatment after blunt thoracic trauma prevents early pulmonary arterial thrombosis without changes in viscoelastic measurements of coagulation. Issue 6 (June 2021) - Schutzman, Linda M.; Rigor, Rob R.; Lin, Yung-Ling J.; Dang, An N.; Le, Peter H.; Singh, Harjeet B.; Yu, Bohan; Wisner, Peter H.; Musson, Cristien C.; Clark, Isaiah J.; Galante, Joseph M.; Brown, Ian E.
Abstract : INTRODUCTION: Previously, in a murine model of blunt thoracic trauma, we provided evidence of primary pulmonary thrombosis associated with increased expression of the cell adhesion molecule, P-selectin. In this study, mice are treated with P-selectin blocking antibody after injury to investigate the clinical viability of this antibody for the prevention of pulmonary thrombosis. In addition, viscoelastic testing is performed to investigate if P-selectin inhibition has a detrimental impact on normal hemostasis. METHODS: A murine model of thoracic trauma was used. Mice were divided into sham control and experimental injury groups. Thirty minutes after trauma, mice were treated with the following: P-selectin blocking antibody, isotype control antibody, low-dose heparin, high-dose heparin, or normal saline. At 90 minutes, whole blood was collected for characterization of coagulation by viscoelastic coagulation monitor (VCM Vet; Entegrion, Durham, NC). Mean clotting time, clot formation time, clot kinetics ( α angle), and maximum clot firmness were compared between each treatment group. RESULTS: Mice that received P-selectin antibody 30 minutes after blunt thoracic trauma had four- to fivefold less ( p < 0.001) arterial fibrin accumulation than those that received the isotype control. In both sham and trauma groups, compared with vehicle (normal saline) alone, no statistical difference was noted in any coagulation parameters after injection with P-selectin antibody, isotype control, or low-dose heparin. In addition, blinded histopathological evaluation yielded no difference in hemorrhage scores between injured mice treated with P-selectin blocking antibody and those treated with isotype antibody control. CONCLUSION: This study supports the clinical use of P-selectin blocking antibody for the prevention of pulmonary thrombosis by confirming its efficacy when given after a blunt thoracic trauma. In addition, we demonstrated that the administration of P-selectin antibody does not adversely affect systemic coagulation as measured by viscoelastic testing, suggesting that P-selectin antibody can be safely given during the acute posttraumatic period. Abstract : Supplemental digital content is available in the text.